(untitled) (Research, Society and Development, 2022)
Objective: To investigate therapeutic evidence of Ayahuasca, which is a psychoactive drink obtained from the decoction of two plants of Amazonian origin: Banisteriospsis caapi (Miri vine) and Psychotria viridis (Chacrona), proven in controlled clinical studies in patients with psychiatric disorders. Methodology: This is an integrative literature review focused on clinical trials available in the electronic databases MEDLINE (Pubmed-AdvancedSearch), Trip data base and Lilacs using the descriptors “Ayahuasca, treatment”; “Ayahuasca, clinical study”; “Ayahuasca, psychiatric treatment”. Results: Eight articles published between 2015 and 2021 were selected. Six studies evaluated the use of Ayahuasca in the treatment of recurrent depressive disorder, and two investigated the relationship between Ayahuasca and reduced risk of suicide in patients with recurrent depression. The drink showed rapid and sustained antidepressant effects, improving symptoms of depression, linked or not to suicidal thoughts. Final Considerations: Considering the side effects and the time required for symptom remission of current treatments, it is necessary to consider the potential of alternative and innovative treatments for patients who do not adapt to conventional methods. The results demonstrated in this research need to be replicated in larger studies, and with longer-term follow-up, to assess the long-term efficacy and safety of the substance.